A century of re-exploring CO2 capture solvents. (October 2022) - Brandl, Patrick; Bui, Mai; Hallett, Jason P.; Mac Dowell, Niall
Highlights: We identify a hypothetical ideal solvent to demonstrate the limits of solvent development. The CO2 capture costs of the ideal limiting solvent was estimated to be $26/tCO2 . Further development of aqueous systems unlikely to yield required cost reductions. To deliver affordable carbon capture, a new technology paradigm is required. Synergies between solvent and process design may be exploited to decrease costs. Abstract: Absorption-based separation processes date back over 120 years, and are recognized as being integral to the delivery of deep decarbonisation. Thousands of new solvents have been proposed but have not yet delivered the level of cost reduction which has been widely anticipated. For much of the past 50 years, the scientific community has focused on developing novel aqueous blends of amines. Whilst they outperform benchmark technologies, they ultimately fail to address the fundamental performance limiting issue; the solvents overwhelmingly consist of water. In this contribution, we present a thought-experiment that uses a hypothetical solvent to identify the limit of available cost reductions to 65% over current performance benchmarks, reaching a cost limit of $26/tonCO2 for gas-power.